If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 3x + 47 Reorder the terms: -1 + 6x = 3x + 47 Reorder the terms: -1 + 6x = 47 + 3x Solving -1 + 6x = 47 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -1 + 6x + -3x = 47 + 3x + -3x Combine like terms: 6x + -3x = 3x -1 + 3x = 47 + 3x + -3x Combine like terms: 3x + -3x = 0 -1 + 3x = 47 + 0 -1 + 3x = 47 Add '1' to each side of the equation. -1 + 1 + 3x = 47 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = 47 + 1 3x = 47 + 1 Combine like terms: 47 + 1 = 48 3x = 48 Divide each side by '3'. x = 16 Simplifying x = 16
| 4=-3a+2 | | 3x-28= | | 1-5m=-3 | | y^2-5y+36=y+1 | | y+7=15y | | 8x^3-36x^2+48x-16=0 | | 5.7x^2-3.2x=2 | | 6x-(3x+7)=17 | | 4+2n=7 | | 2(x-2)-3(2x-5)=3x+7 | | 6x-9-8x=9-x+3 | | 5x-8+3x+4=x+7 | | 3(x-2)=5(x+3) | | 8(3*1.6-5)= | | 8(3a-5)= | | 3x-5=5x+3 | | 3x-5=6x+3 | | (a-11)(a+11)= | | 8(x+8)=64 | | 9x^2+30x+7=0 | | x^2+15x-490=0 | | -j+10s-j+12-8s= | | 8-(4x+m)=5(x+6)-2 | | (6x^4+6x^3-9)-(6x^2-4x+5)= | | 17+6y-10+m+7m= | | (-9p^3)(3p^5)= | | -3x+5y=25 | | 3(3y-2)=5(3y+2) | | 6+4m-17g+6m+3g= | | 11-1.5y=x | | 30x+9+9m+14x-3m= | | 4x-5=-2x+16 |